Distribution of mesopredatory fish determined by habitat variables in a predator-depleted coastal system - Bergström, Lena (Mar Biol, 2016)
Shallow nearshore habitats are highly valued for supporting marine ecosystems, but are subject to intense human-induced pressures. Mesopredatory fish are key components in coastal food webs, and alterations in their abundance may have evident effects also on other parts of the ecosystem. The aim of this study was to clarify the relationship between the abundance of coastal mesopredatory fish, defined as mid-trophic level demersal and benthic species with a diet consisting predominantly of invertebrates, and ambient environmental variables in a fjord system influenced by both eutrophication and overfishing. A field survey was conducted over a coastal gradient comprising 300 data points sampled consistently for fish community and environmental data. Results from multivariate and univariate analyses supported each other, demonstrating that mesopredatory fish abundance at species and functional group level was positively related to the cover of structurally complex vegetation and negatively related to eutrophication, as measured by water transparency. Contrary to other studies showing an inverse relationship to piscivore abundance over time, the spatial distribution of mesopredatory fish was not locally regulated by the abundance of piscivorous fish, probably attributed to piscivores being at historically low levels due to previous overfishing. Mesopredatory fish abundance was highest in areas with high habitat quality and positively related to the abundance of piscivores, suggesting a predominance of bottom-up processes. We conclude that, in parallel with ongoing regulations of fishing pressure, measures to restore habitat function and food web productivity are important for the recovery of coastal fish communities in the area. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00227-016-2977-9) contains supplementary material, which is available to authorized users.